Mobilização passiva global como estratégia reabilitadora no paciente crítico com sepse na UTI: respostas da frequência cardíaca e modulação autonômica cardíaca - Garcia, Naiara Molina (Universidade Federal de São Carlos, 2019)
Introduction: The pathogenesis of sepsis causes loss of cardiac autonomic modulation (CAM) and consequently in heart rate (HR). Physical exercise could be able to promote good responses in these variables, however, few information is available in the literature about the acute effects of passive mobilization (PM) of different joint groups on HR and CAM in patients with sepsis. Objectives: To investigate the HR and CAM responses to patients with sepsis submitted to PM of different joint groups. To identify if there is some connection between CAM, inflammatory profile and factors related to the diagnosis of sepsis. Method: Sixteen patients (58 ± 9 years) with sepsis submitted to a global protocol of PM involving ankle, knee/hip, fist, elbow and shoulder joints (3 sets of 10 repetitions, with a total duration of ≈ 15 min). HR and the RR intervals were recorded by a Polar S810i® cardio-frequency meter and the following analysis was performed: (1) pre-mobilization: HR and CAM measurements before the global protocol (1 and 10 minutes, respectively); and HR before the PM of each grouping; (2) during the mobilization: HR peak measurement for each joint groups and CAM throughout the PM procedure); (3) after mobilization: HR and CAM measurements after global protocol (1 and 7 minutes, respectively) and HR recovery for different joint groups. The RR, rMSSD, LF, HF, LF/HF and SampEn variables were considered for CAM analysis. Results: the PM procedure did not imply significant changes in the HR index, regardless of the joint group analyzed [ankle (p = 0.91); knee/hip (p=0.47); fist (p=0.90); elbow (p=0.43); and shoulder (p=0.48)]. Concerning to CAM, a reduction of SampEn (p=0.006) was observed during PM procedure when compared to pre-PM and increased after PM when compared to exercise. Significant CAM correlations were observed with: C-reactive protein (SampEn: r=-0.57); leukocytes (LF rest: r=0.64 and LF during: r=0.56) and PaO2/FiO2 (SampEn: r=0.67). Conclusion: Regardless of the joint group in analysis, the application of PM procedure in patients with sepsis did not imply significant changes in their HR index. However, it induced cardiac autonomic responses when submitted to a global PM. There are connections between increase of inflammatory profile with worse MAC, as well as between better oxygenation and a better MAC.
Global passive mobilization as a rehabilitation strategy in critically ill patients with sepsis in ICU: Heart rate and cardiac autonomic modulation responses
Keywords: Sepse; Disfunção autonômica; Variabilidade da frequência cardíaca; Mobilização precoce; Sepsis; Autonomic dysfunction; Heart rate variability; Early mobilization; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL